Molecular identification of Bulinus spp. intermediate host snails of Schistosoma spp. in crater lakes of western Uganda with implications for the transmission of the Schistosoma haematobium group parasites - Tumwebaze, Immaculate; Clewing, Catharina; Dusabe, Marie Claire; Tumusiime, Julius; Rugunda, Grace Kagoro; Hammoud, Cyril; Albrecht, Christian (Springer Nature, 2019)
Background: Human schistosomiasis is the second most important tropical disease and occurs in two forms in Africa (intestinal and urogenital) caused by the digenetic trematodes Schistosoma mansoni and Schistosoma haematobium, respectively. A proposed recent shift of schistosomiasis above a previously established altitudinal threshold of 1400 m above sea level in western Ugandan crater lakes has triggered more research interest there. Methods: Based on extensive field sampling in western Uganda and beyond and employing an approach using sequences of the mitochondrial barcoding gene cytochrome c oxidase subunit 1 (cox1) this study aims were: (i) iden‑ tification and establishment of the phylogenetic affinities of Bulinus species as potential hosts for Schistosoma spp.; (ii) determining diversity, frequency and distribution patterns of Bulinus spp.; and (iii) establishing genetic variability and phylogeographical patterns using Bayesian inference and parsimony network analyses. Results: Out of the 58 crater lakes surveyed, three species of Bulinus snails were found in 34 crater lakes. Bulinus tropicus was dominating, Bulinus forskalii was found in two lakes and Bulinus truncatus in one. The latter two species are unconfirmed potential hosts for S. haematobium in this region. However, Bulinus tropicus is an important species for schistosomiasis transmission in ruminants. Bulinus tropicus comprised 31 haplotypes while both B. forskalii and B. truncatus exhibited only a single haplotype in the crater lakes. All species clustered with most of the haplotypes from surrounding lake systems forming source regions for the colonization of the crater lakes. Conclusions: This first detailed malacological study of the crater lakes systems in western Uganda revealed pres‑ ence of Bulinus species that are either not known or not regionally known to be hosts for S. haematobium, the causing agent of human urogenital schistosomiasis. Though this disease risk is almost negligible, the observed dominance of B. tropicus in the crater lakes shows that there is a likelihood of a high risk of infections with Schistosoma bovis. Thus, extra attention should be accorded to safeguard wild and domestic ruminants in this region as the population ben‑ efits from these animals.
Keywords: Bulinus forskalii, Bulinus tropicus, Bulinus truncatus, Schistosoma haematobium, Schistosoma bovis, Neglected tropical disease, Schistosomiasis surveillance